Seed-dispersal ecology of tropical montane forests. (3rd August 2016) - Chapman, Hazel; Cordeiro, Norbert J.; Dutton, Paul; Wenny, Dan; Kitamura, Shumpei; Kaplin, Beth; Melo, Felipe P. L.; Lawes, Michael J.
Abstract: Seed-dispersal ecology in tropical montane forests (TMF) differs in some predictable ways from tropical lowland forests (TLF). Environmental, biogeographic and biotic factors together shape dispersal syndromes which in turn influence forest structure and community composition. Data on diaspore traits along five elevational gradients from forests in Thailand, the Philippines, Tanzania, Malawi and Nigeria showed that diaspore size decreases with increasing altitude, fleshy fruits remain the most common fruit type but the relative proportion of wind-dispersed diaspores increases with altitude. Probably corresponding to diaspore size decreasing with increasing elevation, we also provide evidence that avian body size and gape width decrease with increasing altitude. Among other notable changes in the frugivorous fauna across elevational gradients, we found quantitative evidence illustrating that the proportion of bird versus mammalian frugivores increases with altitude, while TMF primates decrease in diversity and density, and switch diets to include less fruit and more leaf proportionately. A paucity of studies on dispersal distance and seed shadows, the dispersal/predation balance and density-dependent mortality thwart much-needed conclusive comparisons of seed dispersal ecology between TMF and TLF, especially from understudied Asian forests. We examine the available evidence, reveal knowledge gaps and recommend research to enhance our understanding of seed dispersal ecology in tropical forests. This review demonstrates that seed dispersal is a more deterministic and important process in tropical montane forests than has been previously appreciated.